Increased vascular inflammation on PET/CT in psoriatic arthritis patients in comparison with controls - Pim A de Jong; Marloes W Heijstek; Julia Spierings; Karijn P M Suijkerbuijk; Nienke J Kleinrensink; Wouter Foppen; Harald E Vonkeman; Mylène P Jansen; Negina Seddiqi; Amin Herman (RMD Open)
Background Patients with psoriatic arthritis (PsA) have an increased risk of cardiovascular disease, possibly due to a chronic inflammatory state.Objectives The main objective of this study was to investigate the difference in vascular inflammation, measured with 18-fluorodeoxyglucose positron emission tomography/CT (PET/CT), in PsA patients and controls. We conducted a secondary analysis to assess the association between clinical parameters of disease activity with vascular inflammation in PsA.Methods We included a total of 75 PsA patients with active peripheral arthritis (defined as ≥2 tender and swollen joints) from an ongoing clinical trial (EudraCT 2017-003900-28) and a retrospective group of 40 controls diagnosed with melanoma, without distant metastases and not receiving immunotherapy. The main outcome measure was aortic vascular inflammation which was measured on PET/CT scans using target-to-background ratios. Clinical disease activity in PsA was assessed with joint counts, body surface area and the Disease Activity index for PsA. Laboratory assessments included C reactive protein and erythrocyte sedimentation rate.Results Vascular inflammation was increased in patients with PsA in comparison with controls (mean target-to-background ratio for entire aorta, respectively, 1.63±0.17 vs 1.49±0.16; p=<0.001). This association remained significant after correction for gender, age, body mass index, mean arterial pressure and aortic calcification (p=0.002). Vascular inflammation was not associated with disease-related parameters.Conclusions Aortic vascular inflammation was significantly increased in patients with active PsA compared with controls. This evidence supports the theory that inflammation in PsA is not limited to the skin and joints but also involves the vascular system.